Diversity and Distribution of Rust Fungi (Pucciniales) Infecting Mulberry (Morus spp.) in the Philippines: A Scoping Review - Abanes, Frederick; Torres, John Raymund (Journal of Interdisciplinary Perspectives, 2026)
Mulberries (Morus spp.) are cultivated widely in climatic zones and are important in food production, medicine, pollution control, and sericulture. Rust fungi (Pucciniales) are obligate plant pathogens, and some species have been reported to infect mulberries, causing ecological and economic impacts. Despite their potential impact, information on the diversity and distribution of rust fungi infection in Morus spp. in the Philippines remains limited. This scoping review aims to map the distribution and diversity of rust fungi (Pucciniales) infecting Morus spp. locally. Reliable online resources, including published articles and reviews from Google Scholar, were used to gather relevant information on Pucciniales infecting Morus spp. in the Philippines, including their taxonomic identities, host associations, and geographic distributions. Two rust fungi species were documented: Gymnosporangium mori and Cerotelium fici. Records were concentrated in a few provinces, indicating limited geographic data. This scoping review highlights the presence of rust fungi species in the Philippines. Overall, this scoping review provides a baseline for disease management in Morus spp. with regard to rust fungi by identifying the rust species known to infect them locally. Given current knowledge on how to identify and manage them, identical measures could be used to prevent future rust-fungal infections in Morus spp. in the Philippines.